Carbon emissions management efficiency evaluation based on indicator information integration and DEA-Malmquist index - Ye, Fei-Fei; Han, Si-Rui; Lu, Hai-Tian (Frontiers in Environmental Science, 2023)
Completeness of indicator information is an important problem that needs to be further studied in carbon emissions management efficiency evaluation. However, this problem do not has sufficient attention in existing studies and there is lack of the total factor productivity analysis, which is an effective method to evaluate the carbon emissions management efficiency change and it has been applied in different fields. Therefore, an carbon emissions management efficiency evaluation model is proposed based on indicator information integration and data envelopment analysis (DEA)-Malmquist index, in which the kernel of the indicator information integration is the evidential reasoning (ER) approach with an indicator weight calculation; the DEA-Malmquist index is introduced to evaluate the efficiency of carbon emissions management and also analyze its total factor productivity based on the integrated indicator information. A case study of 17 corporates in China from 2019 to 2021 is provided to illustrate the analysis of three scopes efficiency distribution, efficiency change and improvement strategy of carbon emissions management. Results show that the proposed model can be used to provide a reference for the improvement effectiveness of carbon emissions management.